การพัฒนาแบบบันทึกปัญหาด้านยาและผลการให้คำแนะนำปรับขนาดยาโดยเภสัชกร ในคลินิกวาร์ฟาริน โรงพยาบาลสวรรค์ประชารักษ์ : The Development of Drug Related Problems Record Forms and Effect of Pharmacist’s Dosage Recommendations at Warfarin Clinic Sawanpracharak Hospital - เมืองแมน, อุทัยวรรณ; ต่วนเทศ, พรนัชชา (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2019)
วัตถุประสงค์ : เพื่อพัฒนาแบบบันทึกปัญหาด้านยาและคำแนะนำปรับขนาดยาวาร์ฟารินโดยเภสัชกร และศึกษาผลการให้คำแนะนำปรับขนาดยาวาร์ฟารินโดยเภสัชกร สถานที่ศึกษา : คลินิกวาร์ฟาริน โรงพยาบาลสวรรค์ประชารักษ์ รูปแบบการวิจัย : การศึกษาเชิงพรรณนาและเชิงทดลองแบบไปข้างหน้า กลุ่มตัวอย่าง : ผู้ป่วยที่ใช้ยาวาร์ฟารินที่มีค่าไอเอ็นอาร์ไม่เข้าเป้าหมายจากคลินิกวาร์ฟาริน ระหว่างวันที่ 1 ตุลาคม พ.ศ.2560 ถึง 31 กรกฎาคม พ.ศ.2561 จำนวน 51 คน วิธีการศึกษา : พัฒนาแบบบันทึกปัญหาด้านยาและคำแนะนำปรับขนาดยาวาร์ฟารินโดยศึกษาข้อมูลปัญหาด้านยาที่พบบ่อยและปัจจัยที่ส่งผลต่อการออกฤทธิ์ของยาวาร์ฟาริน ทดลองใช้และแก้ไขจนเหมาะสม เภสัชกรประเมินปัญหาด้านยาและแนะนำขนาดยาวาร์ฟารินที่เหมาะสมสำหรับผู้ป่วยโดยใช้แบบบันทึกปัญหาด้านยาและคำแนะนำปรับขนาดยา วาร์ฟารินแนบลงในเวชระเบียนผู้ป่วยนอกก่อนส่งผู้ป่วยพบแพทย์คลินิกวาร์ฟาริน ประเมินผลการใช้แบบบันทึกโดยการสัมภาษณ์ทีมสหสาขาวิชาชีพ และประเมินผลการรักษาหลังการบริบาลทางเภสัชกรรม โดยเปรียบเทียบค่าไอเอ็นอาร์ของผู้ป่วย แต่ละรายก่อนและหลังการให้คำแนะนำปรับขนาดยาวาร์ฟาริน วิเคราะห์ข้อมูลโดยใช้สถิติเชิงพรรณนา และ Wilcoxon signed rank test ผลการศึกษา : ผู้ป่วยเป็นเพศหญิง ร้อยละ 58.8 อายุเฉลี่ย 61.5±14.7 ปี ได้รับยาวาร์ฟารินในข้อบ่งใช้โรคหัวใจห้องบนเต้นผิดจังหวะ ร้อยละ 68.6 เภสัชกรได้ให้คำแนะนำจำนวน 79 ครั้ง พบปัญหาด้านยาจำนวน 55 ปัญหา ส่วนใหญ่เป็นปัญหาการเกิดอันตรกิริยาระหว่างยาวาร์ฟารินกับอาหารร้อยละ 29.1 ทีมสหสาขาวิชาชีพมีความเห็นว่าแบบบันทึกช่วยสื่อสารข้อมูลผู้ป่วย มีประโยชน์ในการดูแลผู้ป่วยร่วมกันระดับดีมากร้อยละ 80.0 และเห็นว่าควรใช้แบบบันทึกนี้ในคลินิกวาร์ฟารินร้อยละ 100 แพทย์ให้การยอมรับคำแนะนำปรับขนาดยาวาร์ฟารินโดยเภสัชกรร้อยละ 94.9 เมื่อประเมินผลการบริบาลทางเภสัชกรรมพบอาการไม่พึงประสงค์จากการใช้ยาวาร์ฟารินเท่าเดิม และพบว่าผู้ป่วยมีค่าไอเอ็นอาร์เข้าเป้าหมายเพิ่มขึ้นอย่างมีนัยสำคัญทางสถิติ (p=0.013) สรุป : แบบบันทึกปัญหาด้านยาและคำแนะนำปรับขนาดยาในผู้ป่วยที่ใช้ยาวาร์ฟารินโดยเภสัชกรที่พัฒนาขึ้นเป็นเครื่องมือที่ใช้ในการสื่อสารและส่งต่อข้อมูลผู้ป่วยให้แก่ทีมสหสาขาวิชาชีพ การบริบาลทางเภสัชกรรมและการให้คำแนะนำปรับขนาดยาวาร์ฟารินโดยเภสัชกรช่วยเพิ่มประสิทธิภาพจากการใช้ยาวาร์ฟาริน ในคลินิกวาร์ฟาริน โรงพยาบาลสวรรค์ประชารักษ์ได้ คำสำคัญ : แบบบันทึกปัญหาด้านยา คำแนะนำการปรับขนาดยาโดยเภสัชกร ยาวาร์ฟาริน Abstract Objective : For development of drug related problems and pharmacist’s dosage recommendations record forms for warfarin’s patients and study the result of pharmacist’s dosage recommendations. Setting : Warfarin Clinic Sawanpracharak Hospital Design : Descriptive and experimental prospective study Subjects : 51 warfarin’s patients who out of range of INR target from Warfarin clinic during 1 October 2017 to 31 July 2018. Methods : Develop the drug related problems and pharmacist’s warfarin dosage recommendations record forms by studying the information on common drug related problems and factors affecting the effect of warfarin. Use the record forms and adjust it for appropriate. Pharmacist evaluate drug related problems and recommend the appropriate dosage of warfarin for warfarin’s patients by using the drug related problems and pharmacist’s dosage recommendations record forms in outpatient medical card, before sending patient to meet the physician at warfarin clinic. To evaluate the multidisciplinary care team usage record form by interview. The assessment of outcome of pharmaceutical care by comparing INR level of each patient before and after receiving recommendation for adjusting warfarin dosage. Data were analyzed by descriptive statistics and Wilcoxon signed rank test. Results : 58.8 percent is female patients. The mean age is 61.5±14.7 years old have received warfarin for indication of atrial fibrillation 68.6 percent.79 of drug related problems were reported. We found 55 drug related problems and mostly concerning warfarin-foods interactions 29.1 percent. Multidisciplinary care team has the opinion that record form helps to communicate patient’s information. It has the best benefits for multidisciplinary care team 80.0 percent and continue use this record forms in warfarin clinic 100 percent. Physician totally accepted pharmacist’s dosage recommendations 94.9 percent. Assessment of outcome of pharmaceutical care showed that adverse drug reaction of warfarin remains the same as before and resulted in significant increase of number of patients within INR in target (p=0.013). Conclusion : Drug related problems and pharmacist’s dosage recommendations record forms for warfarin’s patients is a tool to communicate and refer patient’s information to multidisciplinary care team. Pharmaceutical care and pharmacist’s dosage recommendations enhancing an effectiveness outcomes in warfarin clinic. Key words : Drug related problems record forms, Pharmacist’s dosage recommendations, Warfarin